2005
DOI: 10.1007/s00221-004-2149-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning a throwing task is associated with differential changes in the use of motor abundance

Abstract: This study sought to characterize changes in the synergy of joint motions related to learning a Frisbee throwing task and, in particular, how the use of abundant solutions to joint coordination changed during the course of learning for successful performance. The latter information was helpful in determining the relative importance of different performance-related variables (PVs) to performance improvement. Following a pre-test, the main experiment consisted of six subjects practicing a Frisbee throw to a late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 50 publications
7
75
2
Order By: Relevance
“…However, the variance parallel to the UCM actually increased as a proportion of the overall variance. This suggested that the proportional increase with practice was associated with greater ability to exploit the abundant DOF as well as more stability in the outcome of the skill (Yang & Scholz, 2005). They also found that the variance parallel to the UCM decreased over the course of the movement, while the variance orthogonal to the UCM did not.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the variance parallel to the UCM actually increased as a proportion of the overall variance. This suggested that the proportional increase with practice was associated with greater ability to exploit the abundant DOF as well as more stability in the outcome of the skill (Yang & Scholz, 2005). They also found that the variance parallel to the UCM decreased over the course of the movement, while the variance orthogonal to the UCM did not.…”
Section: Introductionmentioning
confidence: 94%
“…If there is a significantly greater proportion of V UCM then the joint configuration is said to have synergy, in that the abundant DOF in the body are used to minimise the variance in the outcome of the skill . This method has been used to investigate pointing (Domkin, Laczko, Djupsjöbacka, Jaric, & Latash, 2005;Domkin, Laczko, Jaric, Johansson, & Latash, 2002), shooting (Scholz, Schöner, & Latash, 2000), sitto-stand (Reisman, Scholz, & Schöner, 2002;Scholz, Reisman, & Schöner, 2001;Scholz & Schöner, 1999), finger force production (Kapur, Zatsiorsky, & Latash, 2010;Martin, Terekhov, Latash, & Zatsiorsky, 2013;Park, Sun, Zatsiorsky, & Latash, 2011;Scholz, Kang, Patterson, & Latash, 2003;Wu, Pazin, Zatsiorsky & Latash, 2012;Wu, Truglio, Zatsiorsky & Latash, 2015), throwing (Yang & Scholz, 2005) and stone knapping tasks (Rein, Bril, & Nonaka, 2013). Results of these studies have differed with respect to practice, skill level and phase of the skill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively common thread of those studies which used the UCM approach to address changes in movement coordination has been a decrease in both components of variance with learning (Domkin et al 2005(Domkin et al ,2002Yang and Scholz 2005). Depending on the study, the decrease in V UCM could be smaller than , equal to (Domkin et al 2005) or greater than (Domkin et al 2002) the decrease in V ORT .…”
Section: Goal-equivalent Joint Configuration Variance Increased In Rementioning
confidence: 99%
“…Most studies in adults revealed a decrease in both components of joint configuration variance (V UCM and V ORT ) with practice. However, the decrease in V UCM could be larger than (Domkin et al 2002), equal to (Domkin et al 2005), or smaller than (Kang et al 2004;Yang and Scholz 2005) the decrease in V ORT with practice. A related experiment using a slightly different approach to distinguish variance components revealed primarily decreases in V ORT in an early stage of practice, leading to a higher ratio of the two components, while V UCM decreased more than V ORT at a later stage .…”
Section: Introductionmentioning
confidence: 99%